The Survey of Community Anxiety During the Emergency Care (Community Activity Restriction Enforcement) Period - Dwiharini Puspitaningsih; Yudha Laga Hadi Kusuma; Nurul Mawaddah (Jurnal Ilmiah Kesehatan, 2022)
In the few months, increased Covid-19 cases in Indonesia forced the government to Emergency CARE (Community Activity Restriction Enforcement) program in Java-Bali. In addition to COVID-19 impact, Emergency CARE also adds anxiety to the community. This paper aims to analyze community anxiety during the Emergency CARE period. It was a descriptive-analytic study with a survey method. The variable was community anxiety during the Emergency CARE period. Sampling used non-probability sampling with convenience sampling technique with 165 respondents scattered in Java and Bali. In addition, this study used the Zung Self-Rating Anxiety Scale (ZSAS) instrument. The results showed community anxiety was mostly respondents (78%) within normal limits, 16% experienced mild, and 6% had moderate anxiety. In conclusion, there is no community anxiety during the Emergency CARE  period. However, the implementation of Emergency CARE potentially causes community anxiety because it has an average anxiety score that exceeds the minimum anxiety score based on the ZSAS instrument assessment. It is necessary to improve information, education, and communication (IEC) regarding preventing Covid-19 transmission and properly handling psychosocial problems in society to lead to a strong family during the pandemic. Furthermore, This survey could be a policy recommendation to follow-up in overcoming community psychosocial problems due to the Emergency CARE program.